Distribution of small hive beetles, Aethina tumida, in Africanized honey bees (Apis mellifera) in different beekeeping areas of Costa Rica - Arguedas Mora, Martha (2020)
The first report of Small Hive Beetles (SHB), Aethina tumida, in Costa Rica was made on August 25, 2015, in La Cruz, Guanacaste, which increased the risk of dispersal to other beekeeping areas in the country. Therefore, in this study 305 colonies belonging to 61 apiaries, located in San Ramón, Alajuela, Costa Rica, were sampled from May to October 2019. In addition, adult beetle samples were analyzed from Ulloa, Heredia and Potrerillos, Liberia, Guanacaste. Five colonies were randomly selected in every apiary. Broods, boxes, combs, and bottom boards were checked for beetle eggs, larvae and/or adults, and for any related signs such as galleries in the combs, and wet appearance of bees, among others. Adult beetles were analyzed at the Bee Pathology Lab of the Tropical Beekeeping Research Center (CINAT-UNA). The 305 colonies evaluated in San Ramón tested negative for SHBs. On the other hand, the presence of A. tumida was confirmed in a wild colony in a house located in Ulloa, Heredia and in an apiary in Potrerillos, Liberia, which is approximately 25 km from the initial beetle focus in La Cruz, Guanacaste. Based on the above, the presence of A. tumida can be confirmed in Africanized honey bee colonies in different beekeeping areas of Costa Rica, with a limited distribution. Given that adult SHB can fly and move with wild swarms and the transhumance of colonies by beekeepers, apiaries must be periodically checked because the current absence in most of the colonies analyzed in the present study can change.